Effect of different drying techniques on the nutritional properties of Hermetia illucens larvae - Vasconcelos, Robson Antônio de; Lima, William James Nogueira; Costa, Diego Vicente da (Seven Editora, 2024)
By 2050, the UN predicts a world population of 9.7 billion. To meet the protein needs of this population, food production will have to increase by 70% and there are several challenges to be overcome to reach this goal. Insects have proven to be a sustainable alternative to meet this protein demand and the black soldier fly (BSF, Hermetia illucens L.) stands out due to its high protein value and ease of rearing. Also, besides being a source of lipids and fatty acids, its nutritional value includes chitin, that acts as a fiber. We analyzed the influence of different drying techniques - fixed bed drying (FB), oven drying (OD), wind tunnel drying (WT) under different temperatures (50; 55 and 60ºC); sun drying (SUN) and microwave drying (MW) at different powers (20 and 50%) - on the final moisture content and on the nutritional value (protein, lipid and ash content) of black soldier fly larvae. A randomised block design (RBD) was used in a factorial scheme (3 x 3) + 3 additional controls. Data were subjected to variance analysis and Tukey’s test and Dunnett’s test were used for comparisons of means. Significant differences were found for lipid content after the application of the drying techniques. The results showed that higher temperatures and conditions tend to favor an increase in lipid content in the dry material. FB drying at 55ºC returned the highest result (35.24%), statistically comparable to FB-60 (35.00%), MW-50 (34.77%) and BV-60 (34.61%) . In contrast, proteins returned higher values in less strenuous conditions. WT at 50ºC (36.42%) and oven drying at the 3 temperatures surveyed (35.71%; 36.10% and 35.49%) provided the highest results for protein. These studies will contribute to the establishment of an efficient means of drying for BSF larvae. We also present a survey on the pre-treatments that should precede drying to ensure the best food safety. DOI:https://doi.org/10.56238/sevened2023.007-055